Case study on emergency disposal of aniline pollution in Zhanghe River. Issue 6 (May 2019) - Sili, Chen; Lishi, Feng; Chaoyi, Pan; Dinghao, Chen; Qingwei, Guo; Sha, Chang; Ji, Wang
Abstract: In view of the frequent occurrence of secondary environmental pollution caused by safety production accidents in China, a typical case of Zhanghe aniline pollution emergencies is selected and a comprehensive and systematic introduction to the emergency disposal technical scheme of this event is introduced, including the emergency target and general idea, situation prediction, response measures and summary of emergency disposal, which can be used for reference for the same type of emergency disposal technology for environmental emergencies in the future.